2020
DOI: 10.1136/neurintsurg-2020-016842
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bodyweight on VerifyNow Aspirin platelet function test: a retrospective review

Abstract: BackgroundAntiplatelet therapy is used to prevent stent thrombosis in intracranial stents, but the optimal dose of aspirin is unknown. This study sought to determine whether the degree of platelet inhibition with aspirin is affected by bodyweight as observed through a platelet reactivity assay.MethodsThis is a retrospective review of patients who underwent neurovascular stent placement and had a VerifyNow Aspirin assay result. The primary outcome was the correlation between the VerifyNow Aspirin result, bodywe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The results suggest increased body weight is independently associated with impaired response to low‐dose aspirin. However, the relationship was not observed in patients who took 300–325 mg of aspirin 15 . In clinical outcome‐observed studies, previous randomized trials 16 have shown that low‐dose (75–100 mg) aspirin in reducing the risks of vascular events and cancer was modified by body weight.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results suggest increased body weight is independently associated with impaired response to low‐dose aspirin. However, the relationship was not observed in patients who took 300–325 mg of aspirin 15 . In clinical outcome‐observed studies, previous randomized trials 16 have shown that low‐dose (75–100 mg) aspirin in reducing the risks of vascular events and cancer was modified by body weight.…”
Section: Resultsmentioning
confidence: 97%
“…However, the relationship was not observed in patients who took 300-325 mg of aspirin. 15 In clinical outcome-observed studies, previous randomized trials 16 have shown that low-dose (75-100 mg) aspirin in reducing the risks of vascular events and cancer was modified by body weight. And patients taking weight-based aspirin may have a reduced incidence of venous thromboembolism following primary total joint arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the efficacy of ticagrelor may be decreased in patients treated with higher aspirin doses (≥300 mg daily) compared with lower aspirin doses (≤100 mg daily) 14. Two NIS studies reported percentages of subtherapeutic VerifyNow aspirin results with daily aspirin doses of 325 mg15 and 81 mg16 that were in a similar range (16.2% and 13.5%, respectively).…”
Section: Discussionmentioning
confidence: 99%